Deep-towed high resolution seismic imaging II: Determination of P-wave velocity distribution. (February 2018) - Marsset, B.; Ker, S.; Thomas, Y.; Colin, F.
Abstract: The acquisition of high resolution seismic data in deep waters requires the development of deep towed seismic sources and receivers able to deal with the high hydrostatic pressure environment. The low frequency piezoelectric transducer of the SYSIF (SYstème Sismique Fond) deep towed seismic device comply with the former requirement taking advantage of the coupling of a mechanical resonance (Janus driver) and a fluid resonance (Helmholtz cavity) to produce a large frequency bandwidth acoustic signal (220–1050 Hz). The ability to perform deep towed multichannel seismic imaging with SYSIF was demonstrated in 2014, yet, the ability to determine P-wave velocity distribution wasn't achieved. P-wave velocity analysis relies on the ratio between the source-receiver offset range and the depth of the seismic reflectors, thus towing the seismic source and receivers closer to the sea bed will provide a better geometry for P-wave velocity determination. Yet, technical issues, related to the acoustic source directivity, arise for this approach in the particular framework of piezoelectric sources. A signal processing sequence is therefore added to the initial processing flow. Data acquisition took place during the GHASS (Gas Hydrates, fluid Activities and Sediment deformations in the western Black Sea) cruise in the Romanian waters of the Black Sea. The results of the imaging processing are presented for two seismic data sets acquired over gas hydrates and gas bearing sediments. The improvement in the final seismic resolution demonstrates the validity of the velocity model. Highlights: Perform deep towed High Resolution velocity determination. Increase seismic imaging performance. Bottom simulating Reflecto.